2015
DOI: 10.1152/ajpendo.00416.2015
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for greater insulin-stimulated glucose uptake in normal and insulin-resistant skeletal muscle after acute exercise

Abstract: Enhanced skeletal muscle and whole body insulin sensitivity can persist for up to 24 -48 h after one exercise session. This review focuses on potential mechanisms for greater postexercise and insulinstimulated glucose uptake (ISGU) by muscle in individuals with normal or reduced insulin sensitivity. A model is proposed for the processes underlying this improvement; i.e., triggers initiate events that activate subsequent memory elements, which store information that is relayed to mediators, which translate memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
98
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(111 citation statements)
references
References 135 publications
7
98
1
Order By: Relevance
“…Here we similarly found that these HF‐fed skeletal muscle membrane/cytoskeletal abnormalities and insulin resistance were improved in exercised mice, and that these exercised mice showed improved glucose tolerance. While it is possible that the beneficial effects we measured could be attributed to a lingering insulin‐mimetic action of exercise, studies suggest that acute exercise‐stimulated glucose transport is mostly reversed by ~2‐3 h postexercise (Cartee 2015b). Regardless, our studies reveal that an aspect of skeletal muscle insulin resistance improved by exercise, whether acute, chronic, or a combination of both, is membrane/cytoskeletal defects that impair GLUT4 regulation by insulin.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Here we similarly found that these HF‐fed skeletal muscle membrane/cytoskeletal abnormalities and insulin resistance were improved in exercised mice, and that these exercised mice showed improved glucose tolerance. While it is possible that the beneficial effects we measured could be attributed to a lingering insulin‐mimetic action of exercise, studies suggest that acute exercise‐stimulated glucose transport is mostly reversed by ~2‐3 h postexercise (Cartee 2015b). Regardless, our studies reveal that an aspect of skeletal muscle insulin resistance improved by exercise, whether acute, chronic, or a combination of both, is membrane/cytoskeletal defects that impair GLUT4 regulation by insulin.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this favorable effect of exercise on mitigating PM cholesterol accumulation/toxicity, other processes underlying increased insulin sensitivity postexercise could exist. For example, several studies raise the possibility that lower glycogen and/or sustained insulin‐independent AS160 phosphorylation postexercise might sensitize skeletal muscle to insulin (reviewed in (Cartee 2015b)). While we did not measure glycogen or AS160 phosphorylation, the importance of decreased glycogen and/or increased AS160 activity toward enhanced insulin‐sensitivity is unclear (Cartee 2015b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations